Whole exome sequencing identified five novel variants in CNTN2, CARS2, ARSA, and CLCN4 leading to epilepsy in consanguineous families - Abdulkareem, Angham Abdulrhman; Zaman, Qaiser; Khan, Hamza; Khan, Sabar; Rehman, Gauhar; Tariq, Nabeel; Ahmad, Mashal; Owais, Muhammad; Najumuddin,; Muthaffar, Osama Yousef; Bibi, Fehmida; Khang, Rin; et al. (Frontiers in Genetics, 2023)
Epilepsy is a group of neurological disorders characterized by recurring seizures and fits. The Epilepsy genes can be classified into four distinct groups, based on involvement of these genes in different pathways leading to Epilepsy as a phenotype. Genetically the disease has been associated with various pathways, leading to pure epilepsy-related disorders caused by CNTN2 variations, or involving physical or systemic issues along with epilepsy caused by CARS2 and ARSA, or developed by genes that are putatively involved in epilepsy lead by CLCN4 variations. In this study, five families of Pakistani origin (EP-01, EP-02, EP-04, EP-09, and EP-11) were included for molecular diagnosis. Clinical presentations of these patients included neurological symptoms such as delayed development, seizures, regression, myoclonic epilepsy, progressive spastic tetraparesis, vision and hearing impairment, speech problems, muscle fibrillation, tremors, and cognitive decline. Whole exome sequencing in index patients and Sanger sequencing in all available individuals in each family identified four novel homozygous variants in genes CARS2: c.655G>A p.Ala219Thr (EP-01), ARSA: c.338T>C: p.Leu113Pro (EP-02), c.938G>T p.Arg313Leu (EP-11), CNTN2: c.1699G>T p.Glu567Ter (EP-04), and one novel hemizygous variant in gene CLCN4: c.2167C>T p.Arg723Trp (EP-09). To the best of our knowledge these variants were novel and had not been reported in familial epilepsy. These variants were absent in 200 ethnically matched healthy control chromosomes. Three dimensional protein analyses revealed drastic changes in the normal functions of the variant proteins. Furthermore, these variants were designated as “pathogenic” as per guidelines of American College of Medical Genetics 2015. Due to overlapping phenotypes, among the patients, clinical subtyping was not possible. However, whole exome sequencing successfully pinpointed the molecular diagnosis which could be helpful for better management of these patients. Therefore, we recommend that exome sequencing be performed as a first-line molecular diagnostic test in familial cases.